2016
DOI: 10.1186/s12913-016-1354-1
|View full text |Cite
|
Sign up to set email alerts
|

Opportunity costs and local health service spending decisions: a qualitative study from Wales

Abstract: BackgroundAll health care systems face the need to find the resources to meet new demands such as a new, cost-increasing health technology. In England and Wales, when a health technology is recommended by the National Institute for Health and Care Excellence (NICE), the National Health Service (NHS) is mandated to provide the funding to accommodate it within three months of publication of the recommendation. Identifying what, in practice, is foregone when new cost-increasing technologies are introduced is impo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 10 publications
(12 reference statements)
0
15
0
Order By: Relevance
“…A further challenge to AWMSG is the increased need for the opportunity cost to be estimated. It is important to identify what is foregone when new cost-increasing technologies are introduced to understand the effects of HTA decisions on the healthcare system [ 56 , 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…A further challenge to AWMSG is the increased need for the opportunity cost to be estimated. It is important to identify what is foregone when new cost-increasing technologies are introduced to understand the effects of HTA decisions on the healthcare system [ 56 , 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the fact that materials cost accounted for a larger proportion of hospital cost suggested that the hospital should strengthen its supervision on the consumption of high-value materials. [ 15 ]…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the core value of the evaluation is the continuous improvement of medical quality based on the patient-centered concept. [ 8 ]…”
Section: S Everal M Ajor M mentioning
confidence: 99%